Pelatihan Dasar-Dasar Digital Marketing Kepada Pelaku Usaha Mikro & Kecil Desa Labuhan Tereng Kecamatan Lembar Kabupaten Lombok Barat - Sulhan hadi; Sudarta Sudarta; Alfian Eikman (JURNAL ABDI MASYARAKAT ILMU PEMERINTAHAN (JAMIN), 2022)
This Community Service is entitled "Training on the basics of Digital Marketing for Micro and Small Business actors in Labuhan Tereng Village, Lembar District". This service is carried out with several objectives, first, to increase awareness about the importance of business digitization for micro and small business actors; second, to provide skills for business actors in Labuhan Tereng Village, Lembar District in the field of Promotion with digital marketing techniques and third, to provide knowledge about market access that can be reached through digitizing product marketing. The methods applied are face-to-face, mentoring and discussion. The results obtained from this Community Service are increased knowledge and skills of Micro and Small Business actors in Labuhan Tereng Village, Lembar District in the field of Digital Marketing.